The biggest snowball fight! - Medearis, Angela Shelf, 1956-; Snider, Jackie (New York : Scholastic, 2001)
A snowball fight leads to a new dance and starts a new town tradition.
G2
Keywords: Snow -- Fiction; Dance -- Fiction; Humorous stories; Stories in rhyme